2011
DOI: 10.1002/sia.3454
|View full text |Cite
|
Sign up to set email alerts
|

A review of Ga+ FIB/SIMS

Abstract: FIB/SIMS analyses has been performed and reported for well over a decade, however, only within limited research groups due to the lack of commercial FIB/SIMS instrumentation. Commercial availability of FIB/SIMS failed mainly due to two reasons: (i) the low secondary ion yields from the primary Ga + source; and (ii) unrealistic expectations in sensitivity detection limits using the small FIB source. Despite the low yields and limits in sensitivity detection limited by the small volume of material analyzed, FIB/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…The focused ion beam (FIB) technique has proven its efficiency in manufacturing semiconductors, metals and metal oxides, with its unique capability for rapid prototyping and high precision [17,18]. The fundamental mechanism of FIB is that highly energetic ions driven by an electrical field knock atoms off the material surface by electro-collision and the recoil action between the ion and target material surface (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…The focused ion beam (FIB) technique has proven its efficiency in manufacturing semiconductors, metals and metal oxides, with its unique capability for rapid prototyping and high precision [17,18]. The fundamental mechanism of FIB is that highly energetic ions driven by an electrical field knock atoms off the material surface by electro-collision and the recoil action between the ion and target material surface (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…Secondary ion mass spectrometry (SIMS) has been used for many years with focused ion bombardment (FIB) to provide analysis through very local sections of materials to depths of many micrometres . This complements, very nicely, the traditional sputter depth profiling of uniform layers where the total depths are generally smaller but where depth resolutions may be superior and may be typically around 1% of the depth sputtered .…”
Section: Introductionmentioning
confidence: 99%
“…To achieve a high spatial resolution sufficient for investigating the state of boron, we used Ga‐focused ion beam (FIB) as the primary source. However, the application of Ga‐FIB‐SIMS to materials research has been limited occasionally, mainly because of the low secondary ion yield from the Ga + primary and the sensitivity using a high spatial resolution FIB source …”
Section: Introductionmentioning
confidence: 99%
“…However, the application of Ga-FIB-SIMS to materials research has been limited occasionally, mainly because of the low secondary ion yield from the Ga + primary and the sensitivity using a high spatial resolution FIB source. [6,7] To overcome these points, we applied a low energy oxygen ion beam prior to the Ga-FIB-SIMS analysis. It has been reported that the positive secondary ion yield is enhanced by oxygen ion implantation and flooding.…”
Section: Introductionmentioning
confidence: 99%